2020
DOI: 10.22239/2317-269x.01333
|View full text |Cite
|
Sign up to set email alerts
|

Contaminação ambiental: influência da sazonalidade na ocorrência de geo-helmintos em área pública de Fortaleza, Ceará

Abstract: Introdução: A contaminação de locais públicos por formas infectantes de parasitos zoonóticos constitui um grave problema de saúde pública a nível mundial. Um elevado número de animais errantes, a sazonalidade e a antropização do ambiente são elementos importantes na disseminação destas infecções parasitárias. Objetivo: O presente estudo avaliou a influência da sazonalidade na contaminação do solo em uma área pública na cidade de Fortaleza, Ceará, por dois gêneros de geo-helmintos (Toxocara spp. e Ancylostoma s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 11 publications
0
2
0
1
Order By: Relevance
“…Araujo et al (2021) concluded that soil contamination by parasites is directly linked to the presence of animals in these environments, due to their feces and favorable environmental conditions. Melo et al (2020) observed potential risk of zoonoses transmission through soil in a population in the Northeast, especially during the dry season. Abe et al (2019) found that integrated control approaches, such as preventive chemotherapy, health education campaigns, improvement in basic sanitation and access to clean and safe water can eliminate neglected tropical diseases.…”
Section: Discussionmentioning
confidence: 94%
“…Araujo et al (2021) concluded that soil contamination by parasites is directly linked to the presence of animals in these environments, due to their feces and favorable environmental conditions. Melo et al (2020) observed potential risk of zoonoses transmission through soil in a population in the Northeast, especially during the dry season. Abe et al (2019) found that integrated control approaches, such as preventive chemotherapy, health education campaigns, improvement in basic sanitation and access to clean and safe water can eliminate neglected tropical diseases.…”
Section: Discussionmentioning
confidence: 94%
“…Soil characteristics, temperature and high humidity, as well as modifications caused by human activity, can directly or indirectly influence the parasite-host relationship, favoring the creation of environments conducive to the transmission of parasite agents, allowing, in the case of geohelminths, the development of eggs and larvae up to the infective stage (Pedrosa et al, 2014;Sotero-Martins et al, 2014). Melo et al (2020) found that the occurrence of geohelminthes in public areas is sensitive to seasonality. A high percentage of parasite evolutionary forms were found in the dry season while rainfall indices in the region negatively influence the total parasite index, suggesting that soil leaching by rainwater might transport these evolutionary forms far from their origin.…”
Section: Resultsmentioning
confidence: 99%
“…Dessa maneira, os estabelecimentos especializados na culinária japonesa começaram a surgir em cidades ocidentais, oferecendo uma gama de pratos à base de peixe cru, típicos desta culinária. Lojas especializadas se fizeram presentes em shoppings dentro da categoria de fast-food, oferecendo até serviço de delivery (MELO et al, 2014).…”
Section: Casos De Parasitas Em Pescados O Mundounclassified
“…Foram examinadas 51 amostras adquiridas em seis supermercados na cidade em abril de 2013, resultados que indicam alto índice de contaminação. Além disso, as estruturas descobertas foram qualificadas quanto à classe parasitária, sugerindo-se o treinamento dos manipuladores para minimizar o risco de contaminação ou surto (MELO et al, 2014).…”
Section: Casos De Parasitas Em Pescados No Brasilunclassified